2015
DOI: 10.1017/s0007114515002597
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of polyphenols in an inflammatory process associated with experimental pulmonary fibrosis in mice

Abstract: Polyphenols have been described to have a wide range of biological activities, and many reports, published during recent years, have highlighted the beneficial effects of phenolic compounds, illustrating their promising role as therapeutic tools in several acute and chronic disorders. The purpose of study was to evaluate, in an already-assessed model of lung injury caused by bleomycin (BLM) administration, the role of resveratrol and quercetin, as well as to explore the potential beneficial properties of a man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 53 publications
4
53
0
2
Order By: Relevance
“…In fact, the inhibition of proinflammatory responses (NO, iNOS, COX‐2, and PGE 2 ) by polyphenols contained in Mexican blackberry ( Rubus spp) extracts has been widely demonstrated, highlighting a significant correlation between antioxidant capacity and NO inhibition (Cuevas‐Rodríguez et al, ). Thus, the antioxidant and antiinflammatory properties of polyphenols, in agreement with previous studies, could be attributed to the reduction of the nitrosative stress and subsequent formation of NO (Impellizzeri et al, , ; Mandalari et al, , ; Paterniti et al, ).…”
Section: Resultssupporting
confidence: 86%
“…In fact, the inhibition of proinflammatory responses (NO, iNOS, COX‐2, and PGE 2 ) by polyphenols contained in Mexican blackberry ( Rubus spp) extracts has been widely demonstrated, highlighting a significant correlation between antioxidant capacity and NO inhibition (Cuevas‐Rodríguez et al, ). Thus, the antioxidant and antiinflammatory properties of polyphenols, in agreement with previous studies, could be attributed to the reduction of the nitrosative stress and subsequent formation of NO (Impellizzeri et al, , ; Mandalari et al, , ; Paterniti et al, ).…”
Section: Resultssupporting
confidence: 86%
“…One of the most interesting activities of polyphenolic compounds is their ability to modulate the macrophage immune response [9]. Several studies have demonstrated that polyphenolic compounds have a certain degree of anti-inflammatory activity [10][11][12]. Geraniin is a polyphenolic compound that has a wide range of bioactive properties, including anti-oxidant activity, protecting from infections, exerting immunological effects, and inducing metabolic changes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that AMO polarization and activation have a crucial role in early inflammatory responses associated with fibrosis induced by SiO 2 (2931). In this study, we examined the expression of F4/80, a macrophage marker, in an in vivo animal model and observed that the expression of F4/80 was significantly increased after 28 d of SiO 2 treatment compared with that in a normal saline (NS) ( Fig.…”
Section: Resultsmentioning
confidence: 99%